The Influence of Investment and Foreign Affairs on Gross Regional Domestic Product in North Sumatra 2001-2020 - Matondang, Khairani Alawiyah; Situngkir, Desry; Sibarani, Juan Charlos; Tobing, Monalisa Lumban (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research is an observational case study with 9 Economic Sectors in North Sumatra Province, with a period of 5 years (2003-2014). The research object consists of 3 variables, namely: Domestic Investment, Foreign Investment and Labor. Hypothesis, it is expected that three variables collectively influence Gross Regional Domestic Product (GRDP) in North Sumatra. Secondary data was obtained from the publication of survey results related to Indonesian Statistics (BPS) with the 2003-2014 time series, thus forming balance sheet data collected, because data variables across time and in various areas were available with a total of 108 cross-sections of data. Data analysis used log linear regression with the help of statistical tests of the E-views 6.0 application program using the selected Fixed Effect Model regression method. The results of this research show that three variables are thought to influence Gross Regional Domestic Product (GRDP) in North Sumatra, assuming ceteris paribus conditions that: Investment, Labor have a positive influence on Gross Regional Domestic Product (GRDP) in North Sumatra. The percentage of Domestic Investment, Foreign Investment and Labor has a positive effect on Gross Regional Domestic Product (GRDP) in North Sumatra.